The conditional association of problematic drinking with suicidal ideation by alcohol expectancies. (September 2020) - Wolford-Clevenger, Caitlin; Bradizza, Clara; Parrott, Dominic; Cropsey, Karen L.; Stuart, Gregory L.
Highlights: Problematic drinking is positively associated with suicidal ideation. Some alcohol expectancies may change the effects of drinking on suicidal ideation. Positive expectancies reverse the problematic drinking-suicidal ideation relation. Low negative expectancies also reverse this association. Abstract: Purpose: Theory has identified alcohol expectancies as a facilitating factor in the association between problematic drinking and suicidal ideation. In the first test of this question, we explored whether the impact of problematic drinking on suicidal ideation depended on alcohol expectancies. Methods: We conducted a secondary analysis of cross-sectional, observational, survey data from a convenience sample of 444 individuals court-ordered to domestic violence intervention programs (69.5% non-Hispanic White; 78.6% Male-identified; M age  = 32.53, SD age  = 10.10). Results: Parallel analysis and exploratory factor analysis revealed a three-factor structure of the Effects of Drinking Alcohol Scale, including alcohol expectancies related to 1) disinhibition and negative mood, 2) positive mood, and 3) physical and cognitive effects. Multiple linear regression employing bootstrapping procedures tested the moderating effects of these expectancies on the association between problematic drinking and suicidal ideation, while controlling for gender and depressive symptoms. Problematic drinking was negatively associated with suicidal ideation at low levels of disinhibition and negative mood expectancies, and this association became more positive as these expectancies increased. Problematic drinking was negatively associated with suicidal ideation at high levels of positive mood and became more positive as these expectancies decreased. Discussion: These preliminary findings suggest that expectancies related to the mood-altering and disinhibiting effects of alcohol may play a role in whether problematic drinking facilitates suicidal thinking. Future intensive longitudinal designs are needed to test whether this moderation is replicated during periods of acute alcohol intoxication and when other psychiatric symptoms are controlled.